Vestibular Dysfunctions in Sudden Sensorineural Hearing Loss: A Systematic Review and Meta-analysis - Yu, Huiqian; Li, Huawei (Frontiers in Neurology, 2018)
Background: Sudden sensorineural hearing loss (SSHL) not only involves cochlear function, but might also be accompanied by vestibular disturbances. The assessment of vestibular function could be of great relevance in SSHL. Objective: To investigate the prevalence of vestibulocochlear lesions in SSHL and the correlation of specific vestibular organs with hearing prognosis. Data sources: A complete literature search of eligible studies in the PubMed and Embase databases was performed. Study Selection: For our aim, studies that focused on vestibular examination in the case of SSHL were retrieved, including caloric tests, cervical vestibular-evoked myogenic potential (cVEMP) tests, or ocular vestibular-evoked myogenic potential (oVEMP) tests. Results: Of the 18 studies included, a caloric test was performed in 16 studies, cVEMP in 13 studies, and oVEMP in 5 studies, and together the studies included a total population of 1,468 subjects. The scores on the Agency for Healthcare Research and Quality (AHRQ) questionnaire ranged from 6 to 11. These results indicated that the most commonly damaged vestibular organ in SSHL was the utricle and superior vestibular pathway (U+S) followed by the lateral semicircular canal and superior vestibular pathway (LSC+S), the saccule and inferior vestibular pathway (S+I), and the cochlea only (C only). The meta-analysis indicated that SSHL patients with vertigo have a statistically increased risk of vestibular organ lesions compared to those without vertigo, including the LSC+S subgroup (OR = 4.89, 95% CI = 1.20–19.93, I2 = 80%, p = 0.03) and the S+I subgroup (OR = 3.58, 95% CI = 1.61–7.95, I2 = 0%, p = 0.002). The pooled possibility of hearing recovery within the LSC+S lesion group was less than half that of the non-LSC+S lesion group (OR = 0.24, 95% CI = 0.11–0.52, I2 = 68%, p = 0.0003). Conclusion: This study shows the relevance of vestibular damage concomitant with SSHL and that SSHL patients with vertigo are at an increased risk of vestibular organ lesions compared with patients without vertigo. LSC+S lesions thus appear to be a critical variable that influence the possibility of hearing improvement in SSHL.